2023
DOI: 10.1186/s12885-023-10633-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of substance P, neurokinin 1 receptor, Ki-67 and pyruvate kinase M2 in hormone receptor negative breast cancer and evaluation of impact on overall survival

Abstract: Background Chronic inflammation is a hallmark of cancer, and it can be stimulated by many factors. Substance P (SP), through binding to neurokinin 1 receptor (NK1R), and pyruvate kinase M2 (PKM2) play critical roles in cancer development and progression via modulating the tumor microenvironment. This study aimed to investigate the prognostic significance of SP and PKM2 in combination with NK1R and Ki-67 in hormone receptor negative (HR-ve) breast cancer. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…Ki-67, a vital and effective index for evaluating tumor cell proliferation, has been validated as an independent predictor and prognostic factor in breast cancer . Additionally, Ki-67 is notably overexpressed in estrogen receptor (ER)-negative cells. , The counts of Ki-67-positive cells decreased significantly following PM@MOF-Ag NP administration, as shown in Figure B. Furthermore, in vitro flow cytometry and DCF probe staining revealed that PM@MOF-Ag NPs induced ROS overproduction, leading to tumor cell apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Ki-67, a vital and effective index for evaluating tumor cell proliferation, has been validated as an independent predictor and prognostic factor in breast cancer . Additionally, Ki-67 is notably overexpressed in estrogen receptor (ER)-negative cells. , The counts of Ki-67-positive cells decreased significantly following PM@MOF-Ag NP administration, as shown in Figure B. Furthermore, in vitro flow cytometry and DCF probe staining revealed that PM@MOF-Ag NPs induced ROS overproduction, leading to tumor cell apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have demonstrated that NK-1R antagonists counteract the side effects of chemotherapy and radiotherapy and that SP/NK-1R mediate cancer chemoresistance through Notch 1, Raf/MEK/ERK and PI3K/Akt/mTOR and MAPK signaling pathways [7,9,144]. These pathways promote cell proliferation, regulate cell metabolism, block apoptosis, and are crucial in cancer chemoresistance [145,146]. Therefore, the SP/NK-1R system is a potential target to increase the response to anticancer immunotherapies [7].…”
Section: Aprepitant Repurposingmentioning
confidence: 99%